Web-Based Monitoring and Synchronization of Lecturers SKS Information System (Case Study of Muhammadiyah University Cirebon) - Ghina Fauziyyah; Mar’atus Solikhah; Vika Fransisca (Jurnal Indonesia Sosial Teknologi, 2024)
Institutions of higher education are increasingly embracing technology to enhance administrative processes and improve efficiency. This study presents a case study conducted at Muhammadiyah University Cirebon, focusing on the development and implementation of a web-based monitoring and synchronization system for lecturer SKS (Sistem Kredit Semester) information. The system aims to streamline the process of monitoring lecturer workload and credit distribution, thereby optimizing academic resource allocation. Through a combination of qualitative and quantitative research methods, including interviews, surveys, and system evaluation, this study examines the effectiveness and user satisfaction of the implemented system. Findings indicate significant improvements in administrative efficiency, transparency, and data accuracy. Moreover, feedback from users demonstrates a high level of satisfaction with the system's usability and functionality. The study contributes to the body of knowledge on the application of web-based systems in academic institutions and provides insights for similar implementations in other contexts.